The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.17159/2309-8309/2015/v14n3a8
|View full text |Cite
|
Sign up to set email alerts
|

Intramedullary nail after Masquelet bone graft fracture: A case report

Abstract: Large bone defects are challenging to reconstruct and often require specialised treatment strategies, multiple surgeries and long treatment periods. When these bone defects are the result of chronic infection the complexity of the reconstructive process increases exponentially. In the subtrochanteric area of the femur, bone defects secondary to infection are especially challenging as skeletal stabilisation is difficult and internal fixation is considered with caution due to the risk of recurrent infection. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…There is a paucity of literature focusing solely on the reconstruction of non- or malunions following fractures in the proximal femur. In one case study, the Masquelet procedure was reported in a 24-year-old man with osteomyelitis following to subtrochanteric fractures operated on with a plate [49] . In our patient, only superficial wound infection, but not osteomyelitis, was observed shortly after the first operation.…”
Section: Discussionmentioning
confidence: 99%
“…There is a paucity of literature focusing solely on the reconstruction of non- or malunions following fractures in the proximal femur. In one case study, the Masquelet procedure was reported in a 24-year-old man with osteomyelitis following to subtrochanteric fractures operated on with a plate [49] . In our patient, only superficial wound infection, but not osteomyelitis, was observed shortly after the first operation.…”
Section: Discussionmentioning
confidence: 99%